Developing engaged alumni of the future (Terr@ Plural, 2017)
Alumni represent a powerful potential support engine for their Alma mater. This support can be in many forms, for example expanding the university’s network of friends, supporters and strategic contacts, experience sharing in the classroom or at university events, spokespersons at strategic forums, internship opportunities, inkind or financial support for educational activities, mentorship to students, serve in University board of advisors, and reference for prospective students. It can also be in the form of job opportunities, and linkages with industry among other opportunities. Developing the motivation to help their Alma mater has to start before the students arrive to the university for the first day of classes. However, it is, the continued communication and engagement after graduation what will yield the ultimate support of the alumni.